Molecular dissection of quantitative variation in fiber elongation between Gossypium hirsutum and Gossypium barbadense in reciprocal near-isogenic lines - Adhikari, Jeevan; Vitrakoti, Deepak; Ployaram, Wiriyanat; Khanal, Sameer; Chandnani, Rahul; Patel, Jinesh; Shehzad, Tariq; Chee, Peng; Paterson, Andrew H. (Frontiers in Plant Science, 2025)
In reciprocal interspecific near-isogenic lines developed by crossing elite cultivars Acala Maxxa (Gossypium hirsutum) and Pima S6 (G. barbadense) representing the two major domesticated species of cotton, we identified genomic locations underpinning an important fiber quality trait - fiber elongation (ELO). Phenotypic evaluation of these lines in three environments revealed a total of 36 QTLs, including 14 (38.89%) on the D subgenome, from a progenitor that does not produce spinnable fiber. Nearly half (16, 44.4%) of the 36 QTLs identified in the study explained less than 6% of phenotypic variation, and two (EL07.1 and EL25.1) were new, justifying the use of near-isogenic lines for analysis. Significantly larger additive effects of these QTLs in comparison to those reported using early generation backcrosses, F2 and F2 derived populations as well as recombinant inbred lines (RILs) show that NILs offer an advantage in estimating more precise QTL effects by removing background noise due to segregating genomic regions. Seven genomic regions on chromosomes 2, 6, 9, 12, 15 and 18 were consistently associated with ELO in two of the three environments tested. A total of 11 (30.56% of) QTLs had transgressive allele effects, i.e. which were opposite of what would be predicted from the parental phenotypes, indicating opportunities to breed superior interspecific lines; and three QTLs (8.33%) had heterotic alleles that may contribute to the striking fiber quality of F1 hybrids between these species. Limited reciprocity of QTLs in the two backgrounds is attributed to the combined consequences of epistasis, small phenotypic effects and imperfect coverage of donor chromatin in the recipient background. The availability of DNA markers linked to both G. barbadense and G. hirsutum QTLs identified in this and other studies promise to assist breeders in transferring and maintaining valuable traits from exotic sources during cultivar development.